Mindset Sadar Wisata Dalam Tatanan Kehidupan Baru Yang Produktif dan Berdaya Guna Menuju Kemandirian Masyarakat Bagi Penggerak Deswita Jatirejo Gunungpati - Novita Mariana; Saefurrohman Saefurrohman; Dewi Handayani U. N.; Agus Prasetyo Utomo (Universitas Persada Indonesia YAI, 2023)
A village that has the potential as a tourist village for community-based touristdestinations based on the local wisdom of its people, as one of the triggers for theeconomic growth of the community in a rural area that offers an atmosphere of ruralauthenticity both from socio-economic, socio-cultural, customs, daily life, and spatialstructures. a typical village, or economic activity that is unique and interesting and has thepotential to be developed for various components of tourism, such as attractions,accommodation, culinary specialties of food and drink, souvenirs, and other tourist needs.Jatirejo tourist village as one of the tourist destinations is a village in the Gunungpati subdistrictthat is directly affected by the Jatibarang reservoir construction project. A total of62 hectares of agricultural land and plantations owned by residents are affected by thereservoir project. The area of Jatirejo Village in 2014 was 238,130 ha which wasdominated by yards, rice fields and mixed gardens. The large area of land affected by thereservoir project has an impact on activities in the agricultural sector, considering that theagricultural sector is the main source of income for residents in the Jatirejo sub-district.Livelihood data recorded as many as 234 people who work as land-owning farmers, 33people who work as sharecroppers and 427 people who work as farm laborers.With theconstruction of the Jatibarang reservoir which is intended as a tourist destination, theJatirejo village which is located around the reservoir is expected to have a positive impacton the development of the reservoir as a tourist attraction by elevating the Jatirejo touristvillage as one of the village tourist destinations in the city of Semarang. Existing potentialcan be explored without leaving the existing culture. Assistance and facilitation by theservice team in the form of building a community-based mindset and good governance isexpected to grow the existing potential and capabilities to optimize the management ofJatirejo as a tourist village.